DOI: 10.33915/etd.3529
|View full text |Cite
|
Sign up to set email alerts
|

Coyote diets in West Virginia

Abstract: Coyotes were not present in the mid-Atlantic region until the 1950s and little is known regarding their ecology in this region. My objective was to examine the diets of coyotes in West Virginia and to compare diets among regions and seasons as well as between age and sex. I also analyzed the occurrence of livestock in coyote diets and used logistic regression and Akaike's Information Criterion to analyze potential factors influencing livestock consumption by coyotes. In cooperation with the West Virginia Divis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…Ten of our 23 juvenile females (43.5%) were trapped before 3 March (~30 d beyond our average conception date), making it possible that they were pregnant but lacked visible fetuses, as most fetuses are visibly undetectable until 25-30 d. Evaluations of uterine horns for placental scars may have also provided additional information regarding yearling reproduction, but we did not collect uterine tracts. Albers (2012) reported that the average age of sampled coyotes in West Virginia during 2009-2011 was 0.89 y, which may suggest a rapidly growing coyote population in West Virginia. Yearling breeding and evidence of juvenile breeding suggest high resource availability relative to population density.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten of our 23 juvenile females (43.5%) were trapped before 3 March (~30 d beyond our average conception date), making it possible that they were pregnant but lacked visible fetuses, as most fetuses are visibly undetectable until 25-30 d. Evaluations of uterine horns for placental scars may have also provided additional information regarding yearling reproduction, but we did not collect uterine tracts. Albers (2012) reported that the average age of sampled coyotes in West Virginia during 2009-2011 was 0.89 y, which may suggest a rapidly growing coyote population in West Virginia. Yearling breeding and evidence of juvenile breeding suggest high resource availability relative to population density.…”
Section: Discussionmentioning
confidence: 99%
“…We collected and froze coyote carcasses in cooperation with U.S. Department of Agriculture, Animal and Plant Health Inspection Agency Wildlife Services (hereafter Wildlife Services), hunters, and trappers throughout the state of West Virginia as part of a larger coyote diet study (Albers 2012). We recorded location collected, collector's name, and date trapped for each animal.…”
Section: Methodsmentioning
confidence: 99%